Research on estimating the nitrogen pollutant load of agricultural drainage water in the Ningxia irrigation area based on the improved ECM model - Yang, Long; Ou, Yang; Yao, Yao (Frontiers in Environmental Science, 2025)
Agricultural drainage water pollution in Ningxia irrigation areas is a significant factor affecting water quality in the Yellow River Basin. Based on the principle of total nitrogen (TN) input–output conservation, and incorporating irrigation and precipitation correction factors, an improved Export Coefficient Model (ECM) was developed to estimate the TN pollution load from agricultural drainage water. The spatiotemporal distribution characteristics of TN pollution load in Ningxia irrigation districts were analyzed, leading to the following conclusions: 1) from 2010 to 2022, the annual TN export coefficient and multi-year average total load from agricultural drainage water in Ningxia irrigation areas were 26.85 kg/ha·a−1 and 2064.95 t/a, respectively, showing a significant downward trend overall; 2) major changes in the crop structure occurred in Ningxia irrigation areas between 2010 and 2022, with a sharp decline in the rice planting area being the primary factor reducing the pollution load; 3) the spatial distribution of TN pollution load in 2010, 2015, and 2022 exhibited significant heterogeneity, allowing division into high-pollution, medium-pollution, and low-pollution zones. High-pollution zones were primarily located in Pingluo County, Qingtongxia City, and Zhongning County. The improved ECM more accurately reflects actual conditions compared to its predecessor and can support the estimation of agricultural return flow pollution loads in irrigation districts and the management of non-point source pollution in river basins.